ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP NELAYAN DESA PANTAI CERMIN KABUPATEN SERDANG BEDAGAI - Ayu Ardillah (CV. Adiba Aisha Amira, 2023)
Occupational safety and health is an activity to create a safe, comfortable work environment and a way to improve the maintenance of the health of workers both physically, spiritually and socially. Occupational health and safety is specifically aimed at preventing or reducing accidents and their consequences, as well as securing vessels, equipment and catches. The survey used a cross sectional approach by taking a sample of 30 fishermen, the tools used were questionnaires and interviews. Based on the results of the study it was found that the level of knowledge about occupational safety and health obtained with less knowledge was 23 people or 76.7%, and sufficient knowledge was 6 people or 20% good only 1 out of 3.3%, obtained as a large nutritional status was not ever experienced hives, namely 18 or 60% and those who suflered from cataracts 10 or 33.6% who had experienced hypertension/diabetes 2 was 6.7%., nutritional status obtained large itchy disease never experienced, namely 18 people or 60 % and those with cataracts 10 or 33.6% who had hypertension/diabetes 2 was 6.7%.